Leadership Strategies in Management Educational Marketing - Endar Evta Yuda Prayogi (Journal on Education, 2024)
Principal leadership is the ability and readiness of the principal to influence, guide, direct and mobilize school staff so that they can work effectively in order to achieve educational goals. Management is a process for moving, organizing and mobilizing human efforts to achieve goals. Management can also be concluded as a process to move a school institution to carry out its duties. Marketing is a social and managerial process, either by individuals or groups, to obtain what is needed and desired through the creation of offers, the exchange of valuable products with other parties. The aim of this research is to determine the principal's strategy in marketing education at Al Amin Nusantara Islamic Middle School, Central Lampung. The approach that researchers used in this research was a descriptive analysis approach. The data collection techniques that researchers use are observation, interviews and documentation. The results of this research show that the principal's strategy in marketing education at Al Amin Nusantara Islamic Middle School, Central Lampung has implemented a good strategy, the principal has implemented a broad open marketing strategy, target market strategy, competitive position strategy, and mixed strategy. Supporting factors to influence school principals in managing educational marketing include the school principal's high commitment, both with agencies, committees, residents, and also support from other people. The obstacles faced by school principals in educational marketing are the lack of facilities and infrastructure, personnel and also donors who care about the school situation, which can hinder the management of educational marketing.